Canine model of terminal arterial aneurysm. - Graves, V B; Ahuja, A; Strother, C M; Rappe, A H (American Journal of Neuroradiology, 1993)
A canine model of terminal aneurysms using a venous pouch surgical technique is described. This model mimics the anatomy and hemodynamics of some types of carotid and basilar tip aneurysms. This technique produces aneurysms 15 x 21 mm in size. The aneurysms have been used to investigate the hemodynamics and treatment of terminal aneurysms.